2021
DOI: 10.1007/s12098-020-03636-x
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic Lupus with IgA Nephropathy Caused by Spondyloenchondrodysplasia with Immune Dysregulation

Abstract: Monogenic disorders causing systemic lupus erythematosus represent a small subset of cases. Type-1 interferonopathies, like spondyloenchondrodysplasia with immune dysregulation constitute an important functional category of monogenic lupus. Apart from autoimmune disorders, neurological and skeletal abnormalities are additional manifestations observed in this disorder. A young female presented with seizures due to acute hemorrhagic stroke secondary to malignant hypertension. On evaluating the cause for hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…Both parents were identified as heterozygous asymptomatic carriers of one of the variants ( Figures 2B, C ; Supplementary Materials ; Supplementary Table 1 ). Based on the favorable therapeutic response of other patients with type I interferonopathies to JAK inhibitors ( 3 , 4 , 12 , 19 21 ), and the shared pathophysiologic hallmarks of SPENCDI with other type I interferonopathies ( 14 , 22 ), a therapeutic trial with the JAK1/JAK2 inhibitor ruxolitinib was initiated (0.4 mg/kg/day). Within a week from initiation of therapy, the patient reported significantly improved energy levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both parents were identified as heterozygous asymptomatic carriers of one of the variants ( Figures 2B, C ; Supplementary Materials ; Supplementary Table 1 ). Based on the favorable therapeutic response of other patients with type I interferonopathies to JAK inhibitors ( 3 , 4 , 12 , 19 21 ), and the shared pathophysiologic hallmarks of SPENCDI with other type I interferonopathies ( 14 , 22 ), a therapeutic trial with the JAK1/JAK2 inhibitor ruxolitinib was initiated (0.4 mg/kg/day). Within a week from initiation of therapy, the patient reported significantly improved energy levels.…”
Section: Resultsmentioning
confidence: 99%
“…The patient was subsequently referred to an oncologist and diagnosed with smoldering multiple myeloma. These findings prompted a review of the literature that revealed that approximately half of the patients with SPENCDI also report hypergammaglobulinemia ( 2 , 4 , 12 , 13 , 20 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen casos reportados de asociación entre LESJ y (11)(12)(13)(14)(15) NIgA, aunque en su mayoría en adultos , reportándose un caso interesante de Lupus (16) monogénico y NIgA en una adolescente de 15 años . En GWAS, se describen los loci que demuestran asociación entre LES e NIgA: CFH, HLA-DRA, HLA- En este caso, la paciente presentó criterios para LESJ a la edad de 13 años, manifestados por artritis, poliserositis, anemia hemolítica autoinmune, leucopenia, ANA positivo, Anti-DNA positivo, c3 y c 4 b a j o s .…”
Section: Discussionunclassified
“…Mutations in ACP5 and SAMHD1 are known to drive the pathogenesis of SPENCD and AGS, both of which are monogenic interferon diseases characterized by increased type I IFN signaling leading to vasculopathy, autoinflammation, and SLE-like disease (8,23,24). To date, 30 cases of SPENCD with SLE have been reported in the literature (23,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Figure 2A; Table 2), and 9 cases of SLE with SAMHD1 mutations have been reported in the literature (21,(36)(37)(38)(39)(40)(41) (Figure 2B; Table 3), including the patients in this article. Patients with SPENCD or AGS with SLE have a homogeneous clinical presentation, including autoantibody positivity, hematologic involvement, and neurologic symptomatic manifestations.…”
Section: The Germline Rare Mutations Of Acp5 and Samhd1 Identified In...mentioning
confidence: 99%